Cognitive impairment following radiation to hippocampus and other brain structures in adults with primary brain tumours. (July 2020) - Haldbo-Classen, Lene; Amidi, Ali; Lukacova, Slavka; Wu, Lisa Maria; Oettingen, Gorm von; Lassen-Ramshad, Yasmin; Zachariae, Robert; Kallehauge, Jesper Folsted; Høyer, Morten
Highlights: Radiation therapy to the brain and substructures may result in cognitive impairment. Hippocampal radiation may lead to learning and memory impairment. Left sided brain structures may be more vulnerable to radiation. Abstract: Background: Radiation therapy (RT) to the brain may result in cognitive impairment. The primary objective of the present study was to examine the relationship between RT dose to the hippocampus and learning and memory functions. Secondary objective was to examine relationships between doses to other brain structures and specific cognitive functions. Methods: A cross-sectional analysis was undertaken in 78 primary brain tumour patients after RT. Cognitive function was assessed by neuropsychological tests. Test scores were standardized using normative data adjusted for age and level of education. Test-specific cognitive impairment was determined as a z -score ≤−1.5. Radiation dose to brain structures and test-specific cognitive impairment outcomes were fitted to a logistic regression model. Results: High RT dose to the left hippocampus was associated with impaired verbal learning and memory ( p = 0.04). RT dose to the left hippocampus, left temporal lobe, left frontal lobe and total frontal lobe were associated with verbal fluency impairment ( p < 0.05) and doses to the thalamus and the left frontal lobe with impaired executive functioning ( p ≤ 0.03). Finally, RT dose to the brain and thalamus were associated with impaired processing speed ( p ≤ 0.05). Conclusion: The present study indicates that the hippocampus may be vulnerable to radiation and that high radiation doses to the left hippocampus may lead to significant verbal learning and memory impairment. High RT doses to the left hippocampus and other left side structures may result in impairments in verbal fluency, executive function, and processing speed. Validation of these findings are being undertaken in a prospective study.